Chemical Constituents and Health Benefits of Four Chinese Plum Species - Wei Liu; Guangming Nan; Muhammad Farrukh Nisar; Chunpeng Wan (Journal of Food Quality)
Prunus is a large genus in the Rosaceae family of flowering plants, comprising over 340 species inhabiting variable landscapes in the world. Over 500 listed phytochemicals have been isolated from this single genus so far. The present study focused four Chinese Prunus species, viz., Prunus cerasifera, Prunus domestica, Prunus salicina, and Prunus spinosa, due to their uses, demand, nutritional value, medicinal importance, and diverse biological potential. The current review article highlights the details about the active phytochemicals and various pharmacological activities already reported. Almost 212 compounds, the majority of which are flavonoids, phenolic acids, anthocyanins, and their derivatives, which have been isolated from these four Prunus species fall in different categories and are helpful to evade chronic oxidative stress-mediated diseases. A huge variation exists in the total phytochemicals composition in different Prunus species, making these species to have different biological activities in multiple disease conditions, and even the same variety growing under different edaphic conditions may have different antioxidant capacities. It is suggested to perform extensive and indepth studies to find new phytochemicals from these four Chinese Prunus species which could boost the local industry to fulfill the increasing demands.